The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12984-020-00765-4
|View full text |Cite
|
Sign up to set email alerts
|

Activity-based training with the Myosuit: a safety and feasibility study across diverse gait disorders

Abstract: Background Physical activity is a recommended part of treatment for numerous neurological and neuromuscular disorders. Yet, many individuals with limited mobility are not able to meet the recommended activity levels. Lightweight, wearable robots like the Myosuit promise to facilitate functional ambulation and thereby physical activity. However, there is limited evidence of the safety and feasibility of training with such devices. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Wearable exoskeletons are powerful solutions that can be applied to reinforce and enhance mobility in able-bodied subjects [ 1 , 2 ], or to restore lost functions of people with motor problems, such as those resulting from aging [ 3 , 4 ], neurological disorders as spinal cord injury [ 5 7 ], or others [ 8 10 ]. Although these robotic devices are reliable in assisting individuals’ locomotion, researchers still struggle to design smart controllers for exoskeletons that also support balance when needed.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable exoskeletons are powerful solutions that can be applied to reinforce and enhance mobility in able-bodied subjects [ 1 , 2 ], or to restore lost functions of people with motor problems, such as those resulting from aging [ 3 , 4 ], neurological disorders as spinal cord injury [ 5 7 ], or others [ 8 10 ]. Although these robotic devices are reliable in assisting individuals’ locomotion, researchers still struggle to design smart controllers for exoskeletons that also support balance when needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the following sessions an increase of speed and distance was reported for most patients. 18 Robotic-assisted training represents a new, innovative approach in the treatment of heart failure related deconditioning. Previously, the Lokomat® system was tested for gait Figure 3 (A) Ability to perform ADL with and without wearing the Myosuit.…”
Section: Discussionmentioning
confidence: 99%
“…A "transparency" mode of operation allowed the user to turn off the assistance while keeping a slight pre-tension on the tendons. Haufe et al later showed that a revision of the robot -the Myosuit -in transparency mode, does not affect healthy human kinematics [60] and, when active, is a safe and effective tool for training [61], [62].…”
Section: A Tensile Robotic Suitsmentioning
confidence: 99%
“…Similarly, the Myosuit was shown to improve walking speed of a person with incomplete spinal cord injury, by a clinically-meaningful 0.16 m/s [60] and reduce the cost of transport by 9%, compared to a no-suit condition, on an outdoor sloped mountain path [61]. In a feasibility study with eight participants, moreover, Haufe et al showed that the Myosuit is a safe and practical tool for physical training with people suffering from a variety of conditions, including stroke hemiparesis, iSCI and muscular dystrophy [146].…”
Section: A Soft Robotic Suits For Lower Limbsmentioning
confidence: 99%